2016
DOI: 10.2166/wst.2016.376
|View full text |Cite
|
Sign up to set email alerts
|

Sediment deposit thickness and its effect on critical velocity for incipient motion

Abstract: The understanding of how the sediment deposit thickness influences the incipient motion characteristic is still lacking in the literature. Hence, the current study aims to determine the effect of sediment deposition thickness on the critical velocity for incipient motion. An incipient motion experiment was conducted in a rigid boundary rectangular flume of 0.6 m width with varying sediment deposition thickness. Findings from the experiment revealed that the densimetric Froude number has a logarithmic relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In slurry transportation, the minimum hydrodynamic velocity at which particles leave a crack beneath the flow is called the incipient [32][33][34][35][36][37][38] or accumulation velocity. At the incipient velocity, particles start to move by rolling and migration.…”
Section: Model Of Optimal Plugging Flow Ratementioning
confidence: 99%
“…In slurry transportation, the minimum hydrodynamic velocity at which particles leave a crack beneath the flow is called the incipient [32][33][34][35][36][37][38] or accumulation velocity. At the incipient velocity, particles start to move by rolling and migration.…”
Section: Model Of Optimal Plugging Flow Ratementioning
confidence: 99%
“…Detailed studies reported that various criteria for incipient motion of sediment are mainly based on dimensionless shear stress (Beheshti and Ataie-Ashtiani 2008, Cao et al 2006, Cheng 2004 and critical shear velocity (Bong et al 2016, Mao et al 2011, Zhao et al 2013. Various values of dimensionless shear stress were proposed in different literatures, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, shear velocity is another criterion frequently employed to predict incipient motion of sediment. Bong et al (2016) conducted lots of experiments, and analyzed the effect of deposition thickness on incipient motion of sediment according to the criterion for velocity. May (2003) and Zounemat-Kermani et al (2018) reported different kinds of formulas on basis of shear velocity, describing the incipient motion of sediment under different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Selfcleansing is defined by May, Ackers, Butler, and John (1996), Butler, May, and Ackers (2003), and Safari, Aksoy, Unal, and Mohammadi (2017a), as a flow condition in which Research Article accumulated sediment at the channel bottom should be removed (bed sediment motion criteria) or sediment particles which are transported through the flow should be retained in motion (nondeposition criteria). The former covers the "incipient motion" and "scouring" criteria (Bong, Lau, & Ab Ghani, 2013;Bong, Lau, Ab Ghani, & Chan, 2016;Novak & Nalluri, 1984;Safari, Aksoy, Unal, & Mohammadi, 2017b) while the latter includes "nondeposition with and deposited bed, " "nondeposition without deposited bed, " and "incipient deposition" conditions (Aksoy, Safari, Unal, & Mohammadi, 2017;Ota & Nalluri, 2003;Ota & Perrusquía, 2013;Safari, Aksoy, & Mohammadi, 2015Safari & Danandeh Mehr, 2018;Safari, Shirzad, & Mohammadi, 2017;Vongvisessomjai, Tingsanchali, & Babel, 2010). Detailed comparison of the different self-cleansing criteria is reported in Safari, Mohammadi, and Ab Ghani (2018).…”
Section: Introductionmentioning
confidence: 99%